Developmental Competence of Embryo vis-à-vis Lipopolysaccharide - Jinagal, Sujata; Dutt, Ravi; Thakur, Swati; Punetha, Meeti; Sharma, Maninder; Saini, Sheetal; Chaudhary, Suman; Kumar, Pradeep; Yadav, P S; Kumar, Dharmendra (Animal Reproduction Update, 2023)
Post-partum uterine inflammation in dairy bovines impairs the reproductive process  resulting in extended anestrus, reduced conception and increased pregnancy attrition.  Pathogen associated molecular patterns (PAMPs) are a set of molecular motifs that  are present on the surface of various classes of microbes. Bacterial lipopolysaccharides  (LPSs) are an endotoxin found in the cell membranes of Gram-negative bacteria, are  considered as a prototypical class of PAMPs. Among PAMPs, LPS is the most potent  one present on the surface of E. coli associated with endometritis and inflammation of  the uterus. When ovarian follicular cells are exposed to LPS, toll-like receptor (TLR)  and cluster of differentiation 14 (CD14) will be expressed, activating to culminate in  the up-regulation of pro-inflammatory cytokines like IL-1β, IL-18 and TNF which  reacts directly to bacterial products and impairing reproductive functions. Although,  both theca interna and granulosa cells are capable of responding to inflammatory  mediators and altering some functions of the oocytes may result in failure of the oocyte  to become fully competent, even if the insult occurs well before ovulation. Several  studies have been focused on the effect of LPS on the reproductive performance of dairy  animals but the effect of LPS on oocytes during maturation and their development is  yet to be defined well. Therefore, the present review emphasized on the effect of LPS  on important female reproductive functions and possible mechanism of bacterial  endotoxin LPS action on the embryonic development through various pathways.
Keywords: Buffalo; Developmental competence; Embryo; Lipopolysaccharide; Oocytes